Escrita matemática: uma possibilidade para o ensino diferenciado de Álgebra - Sedrês, Aruana da Rosa (2013)
The thesis described here consists of a qualitative research that has been completed in the course of Professional Master s Degree in Mathematics and Science Teaching (UFPel), which I discuss the development of writing in mathematics classes, more specifically the use of writing in the algebraic knowledge. With this practical I seek exercise with student another way to develop mathematical knowledge, regarding what occurs in the classroom, where mathematics is seen only as numbers and operations. The students involved subject of this research are students of 8th grade in a private school in the city of Pelotas/RS and they were chosen to participate in this study case because they have as characteristic the act of belonging to a group that makes studies of progression in Mathematics. To develop the work I use as a methodological option of application in the classroom, in overtime, the Didactic Engineering (Artigue, 1996), a research method which consists of four stages: previous analysis; conception and analysis to priori; experimentation; analysis to posteriori validation of the experimentation. And as a method for analysis of writings completed by these students, in other words, the data analysis using Textual Discoursive Analysis, proposed by Galiazzi and Moraes (2007), allowed to detach in writing these two categories. Activity of writing in mathematics classroom and Learning of Algebra . Such categories confirm what I argue in this thesis, the importance of writing in the classroom. Through the writing students achieve the understanding of how they think and so they establish relations between different meanings and representations of the same notion and/or concept. Through the textual production in class, they are influenced to develop a process with the principles of metacognition (Lafortune and Saint-Pierre, 1996), furthermore, this production arouses student autonomy, improving their understanding, and constitutes as an another mediation between students and knowledge.